A medida socioeducativa em meio aberto na visão dos familiares - Vargas, Thaíse Lopes Grigolo de (2018)
Socio-educational measures comprise a policy of education, accountability, and protection of adolescents in conflict with the law. These measures emerged in Brazil after decades of practices that perpetuated the disfigurement of children and adolescents as subjects of law. These measures were derived from the restructuring of Brazilian politics during the 1988 Constituent Assembly and the creation of the Statute of the Child and Adolescent (ECA) in 1990. The aim of this study was to problematize socio-educational measures in an open environment based on the family members' in conflict with the law. The study was designed as qualitative with descriptive and exploratory character. Data were collected from semistructured interviews. Five family members who accompanied the adolescents in the accomplishment of socio-educational measures in an open environment were interviewed in a Non-Governmental Organization responsible to apply these measures in partnership with the municipality. For the data analysis, the content analysis was used with the development of thematic categories. Participants' responses were grouped into four categories of analysis: Explanation for involvement with the infraction, which discusses how the family members explain the involvement of the adolescent with the infraction; Understanding the process of compliance with an Open Educational Measure, which deals with how the family understands the process of compliance with the measure by the adolescent and projections, which brings the family members' notes about the future of adolescents after compliance with the measures. The categories were discussed based on the Bioecological Theory of Human Development. The results showed that most of the family members believed that the main reason for the involvement of the adolescents in the infraction was the influence of the friends, highlighted by Shoemaker as a process that occurs in the sociopsychological level of development. In relation to the understanding of the compliance process, it is worth mentioning that some family members feel that they are in punitive process. It was also possible to perceive flawed parental monitoring as one of the aspects that influence the offensive behavior of adolescents. Regarding the future perspectives, all hope that adolescents can act professionally, Bronfenbrenner pointed out that this relationship with new contexts enables the individual to complicate development processes. It is noticed that the socio-educational measures allowed the participants of the process different experiences of responsibility for the infraction. Most of the family members presented a positive view about the policy, although some still felt punished during the process of fulfilling the socio-educational measures by the adolescent.